Inside here: daydreaming space and the digital monument - Bosy, Karen (2019)
This paper starts by considering the theories of Henri Lefebvre and Rosalind Krauss to outline an understanding of monumentality, drawing on the theories of the well-respected geographer and theorist Doreen Massey, which support the importance of understanding the relationality of site.  Following on from this, the role of the monument, and the monument’s connection to  imagination and daydreaming, in art practice is explored.  Strategies including Modernist reductionism and unmonumental/anti-monumental art practice are exemplified by artists’ works explicitly concerned with the ‘monument’ and the ‘monumental’, and the questions these works raise are discussed with respect to my own documentarist art practice as represented by artworks included in the Intentions exhibition in 2017: the zine what is public space?, 2017, the moving image artwork, vault, 2017, and collaborative sound artwork Script, 2017.  Key-words: daydreaming, imagination, art practice, monument, relational space